The portrayal of working class people in African novels: a study of Festus Iyayi`s Violence - Abubakar, Mohammed Sani; Mani, Manimangai (Australian International Academic Centre, 2014)
This essay investigates the depiction of the condition of working class people in African novels with particular reference to Violence by Festus Iyayi. The paper examines, first of all, the concept of violence from a Marxist perspective of Franzt Fanon. Furthermore, the paper relates the view of Fanon on violence to what is depicted in the primary text of the paper. The paper argues that the portrayal of the working people in the novel by Iyayi tallies with the view of Fanon in his definition of the concept of violence. The paper exposes how the working people class are presented in the novel as those people who are always in the process of asserting their existence through struggling for survival by selling their labour to the capitalists in order to earn a living. The paper blames this act of suffering on colonialism and neo-colonialism imposed on the African people.